Vascularized and perfusable human heart-on-a-chip model recapitulates aspects of 1 myocardial ischemia and enables analysis of nanomedicine delivery - Kim,J; Zhang,X; Wang,R; Najer,A; Lau,QY; Cammack,A; Kim,JA; Kang,YK; Xie,R; Kim,H; Xie,K; Lim,H; et al. (Advanced Materials, 2025)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide. However, the pathophysiological mechanisms of CVDs are not yet fully understood, and animal models do not accurately replicate human heart function. Heart-on-a-chip technologies with increasing complexity are being developed to mimic aspects of native human cardiac physiology for mechanistic studies and as screening platforms for drugs and nanomedicines. Here, a 3D human myocardial ischemia-on-a-chip platform incorporating perfusable vasculature in direct contact with myocardial regions is designed. Infusing a vasoconstrictor cocktail, including angiotensin II and phenylephrine, into this heart-on-a-chip model leads to increased arrhythmias in cardiomyocyte pacing, fibroblast activation, and damage to blood vessels, all of which are hallmarks of ischemic heart injury. To verify the potential of this platform for drug and nanocarrier screening, a proof-of-concept study is conducted with cardiac homing peptide-conjugated liposomes containing Alamandine. This nanomedicine formulation enhances targeting to the ischemia model, alleviates myocardial ischemia-related characteristics, and improves cardiomyocyte beating. This confirms that the vascularized chip model of human myocardial ischemia provides both functional and mechanistic insights into myocardial tissue pathophysiology and can contribute to the development of cardiac remodeling medicines.